BRCA Mutation Carriers Do Not Have Compromised Ovarian Reserve - Rachel Michaelson‐Cohen; Pnina Mor; Naama Srebnik; Uziel Beller; Ephrat Levy‐Lahad; Talia Eldar‐Geva (2014)
Objective The aim of this study is to evaluate the relation between carrying a BRCA1/2 mutation and fertility using the level of anti-müllerian hormone (AMH), which has been previously shown to be an accurate marker of ovarian reserve and fertility potential. Patients and Methods Forty-one healthy BRCA1/2 mutation carriers, aged 26 to 40 years, attending a multidisciplinary breast and ovarian cancer surveillance clinic, were tested for AMH levels using a 2-site ELISA. Levels were compared with those of our general population and with well-established normograms of the general population. Results The mean age of carriers was 33.2 years (26–39 years; SD, 3.99 years). The mean parity of carriers was 1.97 (0–7; SD, 1.49). All women carried at least 1 Ashkenazi Jewish founder mutation. The AMH levels for most carriers were in the reference range, 2.71 ± 0.59 ng/mL (approximately 50th percentile of normograms). These levels were similar to those in the control group, in which the AMH levels were 2.02 ± 0.12 ng/mL (P = 0.27). Conclusions The AMH levels of healthy BRCA1/2 mutation carriers are similar to those of noncarrier women matched for age; therefore, their ovarian reserve is comparable. This is the only study, to the best of our knowledge, that directly examines ovarian reserve in a relatively large group of carriers with an accurate marker. The results of this study may possibly give reassurance to female carriers concerning fertility potential.